A homeostatic function of CXCR2 signalling in articular cartilage. Issue 12 (18th August 2014) - Sherwood, Joanna; Bertrand, Jessica; Nalesso, Giovanna; Poulet, Blandine; Pitsillides, Andrew; Brandolini, Laura; Karystinou, Alexandra; De Bari, Cosimo; Luyten, Frank P; Pitzalis, Costantino; Pap, Thomas; Dell'Accio, Francesco
Abstract : Objective: ELR+ CXC chemokines are heparin-binding cytokines signalling through the CXCR1 and CXCR2 receptors. ELR+ CXC chemokines have been associated with inflammatory arthritis due to their capacity to attract inflammatory cells. Here, we describe an unsuspected physiological function of these molecules in articular cartilage homeostasis. Methods: Chemokine receptors and ligands were detected by immunohistochemistry, western blotting and RT-PCR. Osteoarthritis was induced in wild-type and CXCR2 −/− mice by destabilisation of the medial meniscus (DMM). CXCR1/2 signalling was inhibited in vitro using blocking antibodies or siRNA. Chondrocyte phenotype was analysed using Alcian blue staining, RT-PCR and western blotting. AKT phosphorylation and SOX9 expression were upregulated using constitutively active AKT or SOX9 plasmids. Apoptosis was detected by terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) assay. Results: CXCL6 was expressed in healthy cartilage and was retained through binding to heparan sulfate proteoglycans. CXCR2 −/− mice developed more severe osteoarthritis than wild types following DMM, with increased chondrocyte apoptosis. Disruption of CXCR1/2 in human and CXCR2 signalling in mouse chondrocytes led to a decrease in extracellular matrix production, reduced expression of chondrocyte differentiation markers and increased chondrocyte apoptosis. CXCR2-dependent chondrocyte homeostasis was mediated by AKT signalling since forced expression of constitutively active AKT rescued the expression of phenotypic markers and the apoptosis induced by CXCR2 blockade. Conclusions: Our study demonstrates an important physiological role for CXCR1/2 signalling in maintaining cartilage homeostasis and suggests that the loss of ELR+ CXC chemokines during cartilage breakdown in osteoarthritis contributes to the characteristic loss of chondrocyte phenotypic stability.